(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Coronavirus diseases (COVID-19) is a respiratory disease. Most infected people are known to develop mild to moderate symptoms and recover without requiring special treatment except for those who have underlying medical conditions and the elderly have a higher risk of developing severe disease. This research is aimed at studying the probable spread of the COVID-19 virus within a completely susceptible density-dependent population using a modified exponential distribution function. The modified exponential distribution function was extended to include the Basic Reproduction Number which was computed using the Nigerian COVID-19 index cases from 27th February to 18th April, 2020 to be. Various interesting results were obtained for the including the time period for the spread for different population sizes. The duration of the spread of the virus is from 4 to 7 hours with an average of 5.5 hours. This indicates that, for one infectious person with to enter a completely susceptible population of size , the virus can spread through the entire population in about hours if no control measures are in place.